We have been given an expression . We have been given steps how Chris tried to solve the given expression. We are asked to choose the correct option about Chris's work.
Let us simplify our given expression.
Using exponent property, , we cab rewrite our given expression as:
Now we will use exponent property to further simplify our expression.
Therefore, Chris made mistake in step 2.
Hey there! :)
Answer:
First option: As x⇒ ∞ f(x) ⇒ -∞. As x⇒ -∞ f(x) ⇒ ∞.
Step-by-step explanation:
Rearrange the equation:
f(x) = -x³ - 2x² + 1
This is a negative cubic function. The function decreases over the interval
(-∞, ∞). Therefore:
As x⇒ ∞ f(x) ⇒ -∞.
As x⇒ -∞ f(x) ⇒ ∞.
This is the first option.
Answer:
10
Step-by-step explanation:
given
we first need to simplify the expression before we find it's value when s=-3
positive times negative=negative
so the equation becomes
substituting s=-3 into the equation.
=
=the negatives cancel out leaving
Im not in geometry class but i can say its B